2020
DOI: 10.3389/fcell.2020.00457
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transcription Factor 21 in Epicardial Cell Differentiation and the Development of Coronary Heart Disease

Abstract: Transcription factor 21 (TCF21) is specific for mesoderm and is expressed in the embryos' mesenchymal derived tissues, such as the epicardium. It plays a vital role in regulating cell differentiation and cell fate specificity through epithelial-mesenchymal transformation during cardiac development. For instance, TCF21 could promote cardiac fibroblast development and inhibit vascular smooth muscle cells (VSMCs) differentiation of epicardial cells. Recent large-scale genome-wide association studies have identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 73 publications
(87 reference statements)
3
18
0
Order By: Relevance
“…However, AP-1 motifs are common within regulatory sequences (Umer et al, 2019), and thus a requirement for these motifs might not reflect specificity for regeneration-related gene expression. Other enriched motifs highlight pathways and TFs known to regulate epicardium development and/or regeneration: Tcf21 (Hu et al, 2020), Hippo/Yap pathway (TEA domain family members, TEADs) (Xiao et al, 2018), C/EBPb (CCAAT/enhancer-binding protein b)(Huang et al, 2012), Tgfβ pathway (Smad2/3/4) (Chablais and Jazwinska, 2012), Hedgehog pathway (GLI family zinc finger 2, Gli2) (Choi et al, 2013; Sugimoto et al, 2017; Wang et al, 2015). Additional implicated TFs that have not been connected to epicardial functions include NFATC1 (Nuclear Factor of Activated T Cells 1), Nrf2 (Nuclear factor-E2-related factor 2), Stat3, FoxO1 (Forkhead box O1), FoxO3, FoxO6, and ZBTB7A (Zinc Finger and BTB Domain Containing 7A) (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…However, AP-1 motifs are common within regulatory sequences (Umer et al, 2019), and thus a requirement for these motifs might not reflect specificity for regeneration-related gene expression. Other enriched motifs highlight pathways and TFs known to regulate epicardium development and/or regeneration: Tcf21 (Hu et al, 2020), Hippo/Yap pathway (TEA domain family members, TEADs) (Xiao et al, 2018), C/EBPb (CCAAT/enhancer-binding protein b)(Huang et al, 2012), Tgfβ pathway (Smad2/3/4) (Chablais and Jazwinska, 2012), Hedgehog pathway (GLI family zinc finger 2, Gli2) (Choi et al, 2013; Sugimoto et al, 2017; Wang et al, 2015). Additional implicated TFs that have not been connected to epicardial functions include NFATC1 (Nuclear Factor of Activated T Cells 1), Nrf2 (Nuclear factor-E2-related factor 2), Stat3, FoxO1 (Forkhead box O1), FoxO3, FoxO6, and ZBTB7A (Zinc Finger and BTB Domain Containing 7A) (Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…To further explore how these gene expression changes might have happened, we next performed transcription factor (TF) target enrichment analysis to identify potential upstream TFs responsible for observed changes in gene expression of Nutlin-3-treated Fmr1 KO mice. Our analysis showed that the top TFs are mainly involved in stem cell fate specification (such as MEOX1, MEOX2, PRRX1, BNC2, SOX18 and TWIST1) [4751] and/or extra cellular matrix organization (such as HEYL, TBX18, PRRX1, PRRX2 and TCF21)[5254] ( Fig. 6a;; Additional file 3: Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At transcriptional level, three distinct transcription factors have been reported to play essential roles in proepicardium and epicardium development, namely, Tcf21, Tbx18 and Wt1. Tcf21 is a transcription factor of the “helix-loop-helix” (HLH) family that is expressed in different tissues derived from the mesoderm, including therein the epicardium [ 213 , 214 ]. In the epicardium, one of the main functions of Tcf1 is to regulate the EMT and the subsequent differentiation and specification of cells derived from the epicardium (EPDC) towards different cell types [ 214 ].…”
Section: Post-transcriptional Control Of Proepicardium/epicardium For...mentioning
confidence: 99%